Genetic tagging of male North Atlantic minke whales through comparison of maternal and foetal DNA-profiles - Skaug , Hans J.; Oien , Nils (J. Cetacean Res. Manage., 2023)
DNA-profiles from 288 mother-foetus pairs were used to obtain partial DNA-profiles for the fathers of the foetuses. The paternal profiles were subsequently matched against those of the males on the Norwegian DNA-register for minke whales using statistical analyses. Three likely instances of paternity were identified. An estimate of the number of reproductively active males in the population was calculated and found to be consistent with previous abundance estimates. However, the associated confidence interval was very broad since it was based on few ‘recaptures’. Finally the scope and potential use of such genetic and population data is discussed.